Assessment of Cascading Accidents of Frostbite, Fire, and Explosion Caused by Liquefied Natural Gas Leakage. (26th August 2020) - Yue, Chengjun; Chen, Li; Xiang, Hengbo; Xu, Linfeng; Yang, Shigang; Li, Zhan; Xia, Chenxi; Fang, Qin
Abstract : Liquefied natural gas (LNG) leaks often lead to cascading accident disasters, including vapor cloud release, explosion, fire, and toxic gas release. The origin and evolution of each accidental disaster must be considered when assessing safety. This paper discusses the safety assessment project of an LNG gas storage station in Xuzhou, China. Multiple conceivable disasters due to the leakage of LNG storage tanks are simulated and analyzed using the computational fluid dynamic software FLACS. We studied different wind speeds interacting with the flammable vapor cloud area and creating frostbite in areas of low temperature. Diffusion simulations of vapor cloud explosion (VCE), thermal radiation, and the distribution of toxic substances were performed. The overpressure-impulse criterion was used to calculate the influence range of VCE. Heat flux, heat dose, and heat flux-heat dose criteria were used to calculate the safe distance for personnel in the event of fire. Based on the calculation results of the three latter criteria, this paper recommends using the heat flux criterion to evaluate fire accidents. The danger zone of each accident was compared. VCE accidents yielded the largest area.